Modeling crop-livestock interactions in semi-subsistence economies - Aragie, Emerta A.; Thurlow, James (Wiley, 2026)
Climate and weather shocks pose significant threats to crop and livestock systems, leading to economic losses and humanitarian crises. Utilizing a modeling framework that innovatively integrates the crop and livestock production systems in semi-subsistence economies, this study examines the interactions and dynamic adjustments within these systems following weather shocks, using Ethiopia as a case study. We also evaluate the effectiveness of various adaptation strategies in sustaining farm incomes, food security, and welfare. Results show unique effects on the crop and livestock sectors resulting from a joint shock on the two systems. While food crops experience a strong and immediate growth effect (12.4%) that fades quickly, the livestock sector faces the full impact of the shock a year later (13.7%), with the effect persisting to some degree. We also find diverging economic and livestock system adjustment trajectories from separate shocks to the crop and livestock systems. Further, the intervention options analyzed show contrasting impacts on various outcome indicators, with only the resilient crop intervention causing sector-indifferent impacts. Our findings emphasize the importance of proactive measures to enhance the resilience of crop-livestock systems, with implications for policy and practice aimed at safeguarding food security and livelihoods in semi-subsistence economies.